Maximum value in triangle#1

Geometry Level 4

In the triangle A B C ABC , B C = a , A C = b , A B = c BC=a, AC=b, AB=c , r r and R R are the radii of the circles that inscribes and circumscribes triangle A B C ABC respectively.

If a b c a\ge b\ge c and a + b 3 c a+b\ge 3c , find the maximum value of r R \dfrac { r }{ R } .

1 2 \frac { 1 }{ 2 } 3 4 \frac { 3 }{ 4 } 4 9 \frac { 4 }{ 9 } 1 3 \frac { 1 }{ 3 }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Linkin Duck
Apr 3, 2017

There are 2 formulas related to r r and R R should be using:

+) The radius of triangle's incircle is given by

r = 2 × A r e a P e r i m e t e r = 2 p ( p a ) ( p b ) ( p c ) a + b + c r=\frac { 2\times Area }{ Perimeter } =\frac { 2\sqrt { p\left( p-a \right) \left( p-b \right) \left( p-c \right) } }{ a+b+c } (applying Heron's Formula for the area of a triangle where p p is half the perimeter, or a + b + c 2 \frac { a+b+c }{ 2 } )

r = 1 2 ( b + c a ) ( a + c b ) ( a + b c ) a + b + c \Longrightarrow r=\frac { 1 }{ 2 } \sqrt { \frac { \left( b+c-a \right) \left( a+c-b \right) \left( a+b-c \right) }{ a+b+c } }

+) The radius of triangle's circumcircle is given by

R = a b c ( a + b + c ) ( b + c a ) ( a + c b ) ( a + b c ) R=\frac { abc }{ \sqrt { \left( a+b+c \right) \left( b+c-a \right) \left( a+c-b \right) \left( a+b-c \right) } }

From 2 above formulas, r R = ( b + c a ) ( a + c b ) ( a + b c ) a b c \frac { r }{ R } =\frac { \left( b+c-a \right) \left( a+c-b \right) \left( a+b-c \right) }{ abc }

Let f ( c ) = ( b + c a ) ( a + c b ) ( a + b c ) a b c f\left( c \right) =\frac { \left( b+c-a \right) \left( a+c-b \right) \left( a+b-c \right) }{ abc }

f ( c ) = ( a + b ) c 2 2 c 3 + ( a + b ) ( a b ) 2 2 a b c 2 ( a + b 2 c ) c 2 2 a b c 2 > 0 \Longrightarrow f^{ ' }\left( c \right) =\frac { \left( a+b \right) { c }^{ 2 }-2{ c }^{ 3 }+\left( a+b \right) { \left( a-b \right) }^{ 2 } }{ 2ab{ c }^{ 2 } } \ge \frac { \left( a+b-2c \right) { c }^{ 2 } }{ 2ab{ c }^{ 2 } } > 0

So, f ( c ) f\left( c \right) is increasing in term of c c .

Since a + b 3 c c a + b 3 a+b\ge 3c\Longrightarrow c\le \frac { a+b }{ 3 }

f ( c ) f ( a + b 3 ) = 4 ( 2 b a ) ( 2 a b ) 9 a b = 4 9 2 ( a b ) 2 9 a b 4 9 \Longrightarrow f\left( c \right) \le f\left( \frac { a+b }{ 3 } \right) =\frac { 4\left( 2b-a \right) { \left( 2a-b \right) } }{ 9ab } =\frac { 4 }{ 9 } -\frac { 2{ \left( a-b \right) }^{ 2 } }{ 9ab } \le \frac { 4 }{ 9 } , or r R 4 9 \frac { r }{ R } \le \frac { 4 }{ 9 }

We then have ( r R ) m a x = 4 9 { \left( \frac { r }{ R } \right) }_{ max }=\frac { 4 }{ 9 } when a = b = 3 2 c a=b=\frac { 3 }{ 2 } c .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...